Morphological and Lexical Contrastive Analysis of Turkish and English (Global Journal of Human-Social Science, 2012)
This study explores the differences and similarities between Turkish and English in the areas of morphology and lexical meaning The discussion leads to different major conclusions Personal endings -im I -sin you singular -dir he she it -iz we -siniz you plural -ler they which stand for Be and NP subject in Turkish are attached to nouns and adjectives as the following examples Ben retmenim ben retmen m - im attached to noun I teacher personal suffix stands for Be -im I am ateacher BenHastay m ben h st j m - m attached to adjective I sick y buffer sound between two vowels personal suffix stands for Be -im I am sick Ben I in both examples could be omitted without changing the meaning because of the personal endings as follows retmenim retmen m teacher personal suffix -im stands for Be and the subject I am a teacher The personal endings stated above are attached to the word de il de l not to make the present tense Be negative as the following example Ben hasta de ilim ben h st de l m I sick negative morpheme de il personal suffix stands for Be -im I am not sick Such conclusions are helpful in language teaching materials syllabuses and test construction
Keywords: Hamlet; Polar concept; Meaning; Balance